Enhancing Bumdes Performance Through Entrepreneurial Communication: An Action Research Approach - Muhammad Setiawan Kusmulyono; Taufik Raharjo (INJECT (Interdisciplinary Journal of Communication), 2025)
The significance of villages position in national growth provides them with a fascinating subject of discussion. Badan Usaha Milik Desa (Bumdes) are operationalized under the Rural Act, increasing village autonomy. Unfortunately, a lot of Bumdes remain stranded because of management issue to business quality to financial resources. In order to assist Bumdes develop more effectively, this study uses an action-research approach to investigate Bumdes with active engagement as a research subject. By applying the seven steps of the soft-system technique to Bumdes experiencing issues with business performance, researchers took an active part in the study. As it was put into practice, it became clear that the realization of close communication between the Bumdes director and village head was just as important to the transformation’s success as entrepreneurial endeavors. Positive interactions between the two parties are essential for Bumdes’ development into an organization that makes greater contributions to the village.